IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA DI SMAN 1 TENJOLAYA - Ihsan, Muzhir; Cahyaningrum, Siti Indah; Supriatna, Nana (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
One way to achieve excellence in education at schools is by ensuring the availability of facilities and infrastructure that support the learning process. The management of these facilities and infrastructure is crucial because it directly impacts the quality of teaching by the teachers in the classroom. Research through the Learning Environment Improvement Program (PLP) at SMAN 1 Tenjolaya aims to describe the actual condition of facilities and infrastructure management at the school. This research uses a descriptive qualitative method with data collection techniques through interviews, documentation, and observation. The subjects of this research are the educational staff responsible for facilities and infrastructure at SMAN 1 Tenjolaya, Bogor Regency. The research results indicate that the management of facilities and infrastructure at SMAN 1 Tenjolaya has been well implemented, where available resources are utilized.